Epicardial Ablation For Ventricular Tachycardia - Maccabelli, Giuseppe (Indian Heart Rhythm Society, 2012)
Epicardial ablation has lately become a necessary tool to approach some ventricular tachycardias in different types of cardiomyopathy. Its diffusion is now limited to a few high volume centers not because of the difficulty of the pericardial puncture but since it requires high competence not only in the VT ablation field but also in knowing and recognizing the possible complications each of which require a careful treatment. This article will review the state of the art of epicardial ablation with special attention to the procedural aspects and to the possible selection criteria of the patients